KONFLIK LAHAN ANTARA MASYARAKAT DENGAN PT. INTI KAMPARINDO SEJAHTERA (STUDY KASUS PADA LOKASI LAHAN DI DESA DANAU LANCANG KECAMATAN TAPUNG HULU KABUPATEN KAMPAR ) - Regar, Nella; Asriwandari, Hesti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This research was conducted in the village Danau Lancang Kecamatan Tapung Hulu Kabupaten Kampar with the aim to obtain information about land conflicts between communities and PT. Inti Kamparindo Sejahterah. Some of the problems in this study were (1) How is the source of conflict in the village of Danau Lancang Districts Tapung Hulu Kampar district? (2) What forms of conflict that occurred in the village of Danau Lancang Districts Tapung Hulu Kampar district? (3) How to conflict resolution in the Village of Danau Lancang Districts Tapung Hulu Kampar district?. The title of this research is